Substituting a substitute currency: The case of Estonia - Kari Heimonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
This study evaluates substitution of foreign currency balances in Estonia, a transition economy neighbouring countries participating in EMU.The focus is on substitution between dollar and euro balances in the three basic functions of money - unit of account, store of value and means of payment.While traditional models for currency substitution concentrate on substitution between a domestic currency and aggregate foreign currency balances, we look for substitution between the dollar and the euro or euro-related foreign currency balances.We find substitution between dollarization and euroization to be asymmetric in the short run, which suggests that inertia, irreversibility and ratchet effects favour the euro.No significant evidence of asymmetries in the long run was detected.In general, the traditional model for currency substitution explains the dynamics of the euro and dollar as substitute foreign currencies.
URN:NBN:fi:bof-201408072199
Keywords: 330